100kW grid-connected renewable energy system design for an educational campus in Tarlac: A step towards green energy campus development. Issue 1 (March 2021) - Rombaoa, Adam
Abstract: This paper discussed the design of a grid-connected renewable energy system for an education institution. One-year energy consumption and the hourly load of the institution were determined to design the energy system. HOMER Pro and What's Best! 16.0 for Microsoft Excel optimization tools were used in the design, consisting mainly of wind turbines and solar PV. Weibull probability function and the simplified irradiance model were used to predict the wind turbine and solar PV power output in the Microsoft Excel spreadsheet. Results showed that the mean velocity at 50 m reference height is 3.886 m/s. The annual solar PV system energy produced based on the HOMER Pro simulation and What's Best! was found to be 170, 939 kWh/yr and 189, 454 kWh/yr, respectively. HOMER Pro and What'sBest! iteration results showed that the optimum number of components are 303 and 0 for solar PV and wind turbine, with net present costs of Php 23, 388, 612 and Php 22, 769, 478, respectively. With this optimum result, emissions can be reduced by up to 51%, a financial saving of at least Php 1, 970, 145 per year can be achieved with payback period of 5 years.